Propuesta un sistema de control interno en las áreas de tesorería y cartera de la compañía Ci Macrometales S.A.S basado en el modelo coso I. (2020)
Propose an internal control model for the treasury and portfolio areas in the company CI MACROMETALES SAS, based on the COSO I model to reduce risks and provide the Administration with a decision-making tool.